“Pasar Cah Cilik” Pembuatan Minuman Es Cincau dengan Penambahan Sari Buah Ide Wirausaha untuk Siswa di SDN 01 Babakan Kecamatan Kramat Kabupaten Tegal - Astriansyah, Lusi Nur (Pena Edukasia, 2023)
Students need higher nutrition, increased growth, and physical development, affecting intake and nutritional needs. It can be overcome with drinks made from natural ingredients. To determine grass jelly drinks' fiber content, nutrition, and acceptability by adding beets and soursop. With the addition of natural grass jelly extract, namely beetroot and soursop, the nutritional value of the formulation was tested for fiber content and its relative value. Chopped beet products produce a fiber content of 1.48%, which can be said to be a source of fiber if consumed per 250 ml or around 3.7 g of fiber. This is following BPOM.